Entrepreneurship Education and Social Environment: Key Drivers of Entrepreneurial Interest Among Students - Andika Isma; Bakry Bakry (Pinisi Journal of Entrepreneurship Review, 2024)
This study aims to identify the key determinants of entrepreneurial interest among students, focusing on the influence of entrepreneurship education and the social environment. The research explores both the individual and combined effects of these factors on students enrolled in entrepreneurship programs at Universitas Negeri Makassar. This study is categorized as quantitative descriptive research, utilizing data collected through questionnaires with a Likert scale. The analysis includes descriptive statistical analysis, prerequisite analysis, hypothesis testing, and the determination of the coefficient. The findings indicate that both entrepreneurship education and the social environment have a significant impact on students' entrepreneurial interest, both individually and collectively. These results suggest that the quality of entrepreneurship education and the surrounding social environment play critical roles in fostering entrepreneurial interest among students in entrepreneurship study programs at public universities in Makassar. The study underscores the importance of creating a supportive educational and social environment to encourage entrepreneurial aspirations among students.